Pride & the Italian's proposal - Hewitt, Kate (Harlequin presents, 2021)
"Fiery Liza Benton couldn't have dreamed that after being dragged into the life of the superrich, she'd be thrown into Fausto Danti's path. She can't stand his arrogance...until a totally unexpected night of passion proves just how compatible they can be! Fausto knows their dueling personalities make Liza the last woman he should ever marry--she challenges him at every turn! But their chemistry is inescapable. So this proud Italian is determined to fight fire with fire--by claiming Liza with a shocking proposal..."--